Risk management of European inland waters using macrophyte biomonitoring - Delmail, David (Frontiers in Environmental Science, 2014)
Inland waters are extremely sensitive to inputs of contaminants. Increasing human activities lead to a rise in organic and inorganic pollutants leading to acidification or eutrophication problems. Many aquatic organisms are affected by these contaminants and significant modifications of their community composition have been recorded. As part of the European Water Framework Directive, macrophyte biomonitoring has been developed to assess the quality of waters and their ecological status. The purpose of such studies was to establish the macrophyte-community composition as an indicator of the pollution level using multivariate approaches. As the various macrophyte indices evolve in concordance with European environmental policy needs, spatial and temporal comparisons between aquatic environments from different regions or countries would be possible.